Rancang Bangun Antena Mikrostrip Pattch Rectangular Array 4x1 pada Frekuensi 1800 MHz-2300 MHz - Ruliyanta Ruliyanta; Endang Retno Nugroho (Jurnal Ilmiah Giga, 2021)
4G network is a technology that is currently being developed, known as LTE or 4G. An antenna microstrip for 4G technology is used in this paper. The antenna designed to resonate at a frequency of 1800 MHz-2300 MHz. The antenna design will use FR-4 for its substrate which functions as a dielectric for the antenna. The design is done using the help of CST Studio Suite 2014 software and NI AWR Design Environment v.12 to get the desired antenna characteristics through simulation. From our research we obtained the antenna characteristics such as return loss, VSWR (Voltage Standing Wave Ratio), gain, and bandwidth. In this research, a 4×1 patch rectangular microstrip array antenna has been designed and built that works at a frequency of 2.05 GHz for 4G technology. The antenna design uses the FR-4 for its substrate which functions as a dielectric for the antenna. The design is carried out with the help of CST Studio Suite software to obtain the desired antenna characteristics through simulation. From the research results obtained antenna characteristics such as return loss of -25.225 dB. VSWR (Voltage Standing Wave Ratio) of 1.15, the gain of 3.1 dBi, and bandwidth of 500 MHz with a 4×1 rectangular array antenna design.